Have you switched to a low-carbon diet? The ultimate value of low-carbon consumerism - Yu-Ling Lin; Hong-Wen Lin (Administrative Sciences, 2014)
Since the 1990s many governments around the world have been encouraging their people to participate in green or low carbon living. With the background of rising consumer awareness in environmental protection, green consumption, and green marketing are receiving growing attention from consumers and enterprises. Therefore, the purpose of this paper is to identify the goals and values of 60 Taiwanese consumers in a low-carbon diet. This study uses the theory of Mean-end chain as basis, applying the "Soft-laddering" of "Laddering" to understand the perceived value of low carbon food in depth interviews. The results revealed that the attributes of users care for green living in the, order of, Less meat more vegetables, Seasonal food, Local food, Food with minimal artificial processing, Energy-saving preparation and Carbon footprint. After classifying by content analysis, we draw the Hierarchical value map (HVM) to explore that consumer's pursuit of the final value and benefits by adopting a low-carbon diet relate to healthy living.
Keywords: 350; low-carbon diet; green living; means-end chains; customer value